2020
DOI: 10.1111/cmi.13283
|View full text |Cite
|
Sign up to set email alerts
|

Toxoplasma gondii excreted/secreted proteases disrupt intercellular junction proteins in epithelial cell monolayers to facilitate tachyzoites paracellular migration

Abstract: Toxoplasma gondii shows high dissemination and migration properties across biological barriers infecting immunologically privileged organs. Toxoplasma uses different routes for dissemination; however, the mechanisms are not fully understood. Herein, we studied the effects of proteases present in excretion/secretion products (ESPs) of Toxoplasma on MDCK cell monolayers. Ultrastructural analysis showed that ESPs of Toxoplasma disrupt the intercellular junctions (IJ) of adjacent cells. The tight junction (TJ) pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 44 publications
0
12
0
Order By: Relevance
“…Gene expression of tight junction proteins Zo1 and Occludin , and the key regulator of inflammation Il-22 were measured in the SI (SI2 region). Epithelial barrier dysfunction is characterised by decreased levels of Zo1 and Occludin , which has been observed during Tg infection both at the gene expression (75) and protein levels (76). Transgenic animals lacking Il-22 infected with Tg have higher mortalities than their wildtype counterparts (77).…”
Section: Resultsmentioning
confidence: 99%
“…Gene expression of tight junction proteins Zo1 and Occludin , and the key regulator of inflammation Il-22 were measured in the SI (SI2 region). Epithelial barrier dysfunction is characterised by decreased levels of Zo1 and Occludin , which has been observed during Tg infection both at the gene expression (75) and protein levels (76). Transgenic animals lacking Il-22 infected with Tg have higher mortalities than their wildtype counterparts (77).…”
Section: Resultsmentioning
confidence: 99%
“…To determine the effect of T. denticola infection on tight junctions, Madin-Darby canine kidney epithelial (MDCK) cells NBL-2, which are widely used in epithelial models to investigate tight junctions 21,26,29) , were used. The MDCK cells were obtained from the Health Research Resources Bank (Osaka, Japan) and maintained in α-minimum essential Medium (MEM) supplemented with 10% fetal bovine serum (FBS) (Gibco Life Technologies, New York, NY, USA) and antibodies at 37°C in a humidified 5% CO 2 atmosphere.…”
Section: Cell Culturesmentioning
confidence: 99%
“…It has also been observed that tachyzoites co-localize with the tight junction protein occludin, which appears to facilitate paracellular transmigration of the parasite ( Barragan et al., 2005 ; Weight and Carding, 2012 ). Recent data suggest that paracellular migration is facilitated by parasite secretory proteases that target tight junction proteins ZO-1, occludin, and claudin-1 ( Ramirez-Flores et al., 2020 ).…”
Section: Overview Of Toxoplasma In the Intestinementioning
confidence: 99%